Survey the level of knowledge of female teachers employed in governmental high ‎schools in Some-E- Sara on AIDS in ‎‏2004‏ - fatemeh seyedfazelpour; farideh hasavari; mitra sedghi sabet (Guilan University of Medical Sciences, 2005)
Introduction: AIDS is a major problem in human society and it is a barrier to economical, ‎social and cultural development. The number of AIDS patients had reached its highest in ‎‏2005‏‎ ‎which was ‎‏40300000‏‎ cases. According to official reports in Iran, up to March, ‎‏2005‏‎, there ‎were ‎‏10700‏‎ cases of AIDS. Based on present statistics, this disease is more prevalent in young ‎and in women aging ‎‏15-24‏‎, it is ‎‏20‏‎ percent but in men, it is‏13.5‏‎ percent. This indicates the ‎need to educate students in regard to prevention of AIDS especially girls. In this case, the ‎best places to educate are schools and teachers are the best educators.‎ Objective: The main goal of this study was to determine the level of knowledge of female ‎teachers employed in governmental high schools in Some -E-Sara on AIDS. ‎ Methods: In this descriptive cross - sectional study, a two part questionnaire on AIDS disease ‎and its prevention was used for data collection. The questionnaire was given to all ‎‏110‏‎ ‎employed female teachers and data was analyzed by SPSS.‎ Results: ‎‏58.2%‏‎ of samples were in ‎‏26-35‏‎ age range, ‎‏59.1%‏‎ had work experience between ‎‏5-‏‏15‏‎ years and ‎‏45.5%‏‎ had poor knowledge. There was a significant relation between age, work ‎experience, source of information and knowledge.‎ Conclusion: In attention to findings, it is suggested to plan proper programs, workshops with ‎cooperation of related institutes and also broadcasting simple and interesting TV programs at ‎proper time to improve teachers knowledge so they would be more capable of teaching the ‎young.‎